Qualidade de vida no trabalho: estudo em empresas do setor calçadista da Paraíba - Diniz, Luciene Laranjeira (2010)
The aim of this study was to examine the quality of work life in the business of sports footwear sector João Pessoa - PB. The quality of work life (QWL) according to Nadler and Lawler (1983), is a way of thinking about people, work and organization in view of the impact of work on people and organizational effectiveness, as well as the prospect of some degree of participation in solving problems. Still defined as a dynamic management and contingency of physical, technological and socio-psychological that affect the culture and renew the organizational climate, reflected in the welfare of the worker and the productivity of firms. Management dynamics because the organizations and people are constantly changing, and it is contingent because it depends on the reality of each company in the context in which it operates (FERNANDES, 1996; CONTE, 2003). Considering the importance of this approach for organizations to present research sought to rescue this thread from the structuring of factors that includes the QWL within the reality that these companies are located. This dissertation is structured initially in a theoretical discussion about the QWL and related matters, followed by the methodological procedures and results that research has revealed, and finally the closing remarks. Thus, a study is qualitative and descriptive in character, because it is a clearly defined study on the field and the size to be imaged, and the researcher's intention to better understand the phenomenon of quality of work life through perceptions of individuals involved in the case examined, for an interpretation of reality. In this sense, the research instrument used was a structured questionnaire comprising the categories of the Likert scale, applied to officials at the operational level of production of the companies examined. It was found that the perception of officials of the companies studied the quality of work life is considered good. However, employees of Company A were more satisfied with the QWL of the employees of the company P.